Respuesta :

Answer:

[tex]\sqrt{2}-\sqrt{5}+\sqrt{10}[/tex]

Step-by-step explanation:

we have

[tex]\sqrt{2}-\frac{\sqrt{10}}{\sqrt{2}} +\sqrt{10}[/tex]

we know that

[tex]\sqrt{10}=\sqrt{2}*\sqrt{5}[/tex]

substitute

[tex]\sqrt{2}-\frac{\sqrt{2}*\sqrt{5}}{\sqrt{2}} +\sqrt{10}[/tex]

simplify

[tex]\sqrt{2}-\sqrt{5}+\sqrt{10}[/tex]

Answer:

[tex]\frac{1}{2}(\sqrt{5}-3)[/tex]

Step-by-step explanation:

Given expression,

[tex]\frac{\sqrt{2}-\sqrt{10}}{\sqrt{2}+\sqrt{10}}[/tex]

By rationalising the denominator,

[tex]=\frac{\sqrt{2}-\sqrt{10}}{\sqrt{2}+\sqrt{10}}\times\frac{\sqrt{2}-\sqrt{10}}{\sqrt{2}-\sqrt{10}}[/tex]

[tex]=\frac{(\sqrt{2}-\sqrt{10})^2}{(\sqrt{2})^2-(\sqrt{10})^2}[/tex]

( ∵ ( a + b ) ( a - b ) = a² - b² )

[tex]=\frac{(\sqrt{2}-\sqrt{10})^2}{2-10}[/tex]

[tex]=\frac{2+10-2\sqrt{20}}{-8}[/tex]

( ∵ (a + b)² = a² + 2ab + b² )

[tex]=-\frac{1}{8}(12-4\sqrt{5})[/tex]

[tex]=-\frac{1}{2}(3-\sqrt{5})[/tex]

[tex]=\frac{1}{2}(\sqrt{5}-3)[/tex]